Analysis and treatment of cracks in LPG spherical tank. Issue 1 (March 2021) - Jiang, Chengjun; Du, Yannan; Zhang, Xiaoli; Pan, Weiguo
Abstract: During the first periodic inspection of the LPG spherical tank, a crack was inspected when the inner shell was detected by fluorescent magnetic powder test. The cause of the crack was analyzed by macromorphology examination, chemical composition analysis, hardness test and metallographic examination. Analysis results show that unreasonable welding procedure, no preheating process, improper storage of weld rods result in martensite structure of the welded joint, welding residual stress and diffusible hydrogen, which is the typical characteristic of the welding cold crack. The repair measures are taken to solve the problem and reduce the hidden dangers.